2012
DOI: 10.1038/nsmb.2463
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the mature dengue virus at 3.5-Å resolution

Abstract: Regulated by pH, membrane-anchored proteins E and M play a series of roles during dengue virus maturation and membrane fusion. Our atomic model of the whole virion from cryo electron microscopy at 3.5Å resolution reveals that in the mature virus at neutral extracellular pH, the N-terminal 20-amino acid segment of M (involving three pH-sensing histidines) latches and thereby prevents spring-loaded E fusion protein from prematurely exposing its fusion peptide. This M latch was fastened at an earlier stage, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
456
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(490 citation statements)
references
References 36 publications
15
456
0
2
Order By: Relevance
“…This suggests that the low-pH-induced structural rearrangement of the particle is required to expose the furin cleavage site on prM. Indeed, the currently accepted model of flavivirus maturation within the trans-Golgi involves the stem region of the prM protein interacting with the associated E protein DII in a manner that pulls E down from a trimeric spike into a flat dimeric conformation parallel to the virion surface (Zhang et al, 2012(Zhang et al, , 2013b, with this interaction dependent upon decreasing pH and originating from one or more discrete nucleation centres (Plevka et al, 2011(Plevka et al, , 2014. In addition, the low-pH environment in the trans-Golgi compartment allows the pr peptide to remain associated with E (Yu et al, 2009), effectively preventing premature fusion within the cell.…”
Section: Maturation Of Prm By Furin Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the low-pH-induced structural rearrangement of the particle is required to expose the furin cleavage site on prM. Indeed, the currently accepted model of flavivirus maturation within the trans-Golgi involves the stem region of the prM protein interacting with the associated E protein DII in a manner that pulls E down from a trimeric spike into a flat dimeric conformation parallel to the virion surface (Zhang et al, 2012(Zhang et al, , 2013b, with this interaction dependent upon decreasing pH and originating from one or more discrete nucleation centres (Plevka et al, 2011(Plevka et al, , 2014. In addition, the low-pH environment in the trans-Golgi compartment allows the pr peptide to remain associated with E (Yu et al, 2009), effectively preventing premature fusion within the cell.…”
Section: Maturation Of Prm By Furin Cleavagementioning
confidence: 99%
“…Whereas the structure of the mature M portion of prM has yet to be solved beyond cryo-electron microscopy reconstructions (Zhang et al, 2013b), a crystal structure of the DENV pr peptide has been reported in complex with the soluble ectodomain of E ) (see Figs 1b and 3). The pr peptide forms a tightly folded protein domain consisting of two small b-sheets linked by disulfide bridges, with the entire structure positioned at the distal end of E domain II (DII) within the heterodimer where it obscures the fusion loop and facilitates pr glycan presentation at the tip of trimeric spikes Yu et al, 2008;Zhang et al, 2003).…”
Section: Prm Proteinmentioning
confidence: 99%
“…2c). Therefore, there is only one Asn154 glycosylation site in an E protein in ZIKV, whereas DENV has two (Asn67 and Asn153) 14 . The Asn154 glycosylation site is suggested to be a neurovirulence determinant in WNV 21 ; however, DENV also has this glycosylation site but infection with DENV rarely results in neurovirulence.…”
mentioning
confidence: 99%
“…4b) compared to DENV may increase the overall stability of the virus. For comparison, a similar resolution DENV2 cryoEM structure 14 , which has been shown to be less stable at increased temperatures 9,10 , was used. The Ala340 insertion in the C strand of DIII allows the CD-loop to stretch further towards the five-fold vertex compared to DENV2 (Fig.…”
mentioning
confidence: 99%
“…For example, single-particle reconstruction requires 10 5 particles to reconstruct a near-atomic-resolution structure, as long as the samples have good biochemical properties and high conformational homogeneity [1]. For bio-macromolecule complexes with high symmetry, such as viruses, only 10 4 particles may be needed [11]. A cryo-EM specimen requires 35 L of protein solution at a concentration of 0.11 mol L 1 .…”
Section: Small Samplesmentioning
confidence: 99%